PERSUASIVE DESIGN IN ADVERTISING AS A FACTOR OF INFLUENCE ON THE BEHAVIORAL ORIENTATION OF THE SOCIETY - Kolisnyk, O. V. (Art and Design, 2018)
To analyze the persuasive design of advertising as a now days phenomenon, and also to consider the influence of design meanings-images on the perception processes and behavioral reactions of a person. A combination of complex and comparative methods that allow to identify the peculiarity of the problems of persuasive design of advertising in the modern society, as well as the principles of objectivity and impartiality of analysis, the principle of critical reflection of the investigated material. Results. The content of the persuasive design of advertising in the social everyday life was analysed. It was carried out its characteristic features, such as expressiveness, persuasiveness, speed of the transfer of a certain pragmatic installation, emotional influence on the subconscious reactions of a person, as a result of the possibility of transformation of perception and behavioral social orientation of the target audience with subsequent programming of it action in the future. Findings. We paid attention to the social responsibility of both customers and designers of advertising products for formation the internal intentions and behavioral stereotypes of most representatives of modern society. Practical value. The findings of the study should help to deepen the understanding of the specificity of the persuasive design of advertising as a phenomenon of the presents, its interconnectedness with various aspects of human vitality.